2018
DOI: 10.1039/c8sc02291g
|View full text |Cite
|
Sign up to set email alerts
|

Bright insights into palladium-triggered local chemotherapy

Abstract: We report fundamental insights into the validity, reliability and clinical feasibility of using heterogeneous Pd catalysts as implantable devices to accurately activate chemotherapy within a tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 46 publications
2
102
0
Order By: Relevance
“…Indeed, several groups showed that organometallic activators can be used in the form of nano‐formulations that can be implanted during surgery or has the ability to accumulate at the tumor site based on the enhanced permeability and retention effect. After prodrug administration, these organometallic devices serve to produce the active drugs locally, which can have beneficial therapeutic effect . For intracellular applications, the metal catalyst can be fused to e. g. cell‐penetrating peptides …”
Section: Figurementioning
confidence: 99%
“…Indeed, several groups showed that organometallic activators can be used in the form of nano‐formulations that can be implanted during surgery or has the ability to accumulate at the tumor site based on the enhanced permeability and retention effect. After prodrug administration, these organometallic devices serve to produce the active drugs locally, which can have beneficial therapeutic effect . For intracellular applications, the metal catalyst can be fused to e. g. cell‐penetrating peptides …”
Section: Figurementioning
confidence: 99%
“…[53] Bray et al demonstrated that Pd 0 microdevices have the capacity to carry out ex vivo carbamate cleavage of masked doxorubicin in tumor tissues.T he Pd catalysts showedp romising biocompatibility when implanted in mice bearing prostate tumors and studies on zebrafish revealed that caged doxorubicin avoided the cardiotoxicity typicallyp roduced by the drug alone. [54] Ap ropargyl-masked prodrug of the histone deacetylase inhibitor vorinostat was also activated through Pd 0 catalysis. [55] The deprotection proceeded at physiological pH through at andem mechanism triggered by the Pd-catalyzed depropargylation.…”
Section: Transition-metal-mediated Bioorthogonal Catalysismentioning
confidence: 99%
“…Cells were independently treated with Pd‐microdevices (1 mg mL −1 ) or 2 c (−ve controls) or in combination (activation assay) and compared to treatment with unmodified 1 (+ve control) across a range of concentrations. As expected, the devices (which are larger than cells and remain in the extracellular space) displayed no toxic effect. In contrast, the Pd‐devices/ 2 c combination led to potent antiproliferative effect in all cell lines, slightly lower than that mediated by direct treatment with 1 .…”
Section: Resultsmentioning
confidence: 76%
“…Palladium (Pd) catalysts are one of the tools of choice currently under investigation to release caged drugs in vitro and in vivo . The selection of this metal is based on its high bio‐compatibility, its versatility to adopt different shapes and sizes and its remarkable capabilities to catalyze N ‐ and O ‐dealkylation reactions on manifold types of substrates under physiological conditions .…”
Section: Introductionmentioning
confidence: 99%